Hemadsorption as a Treatment Option for Multisystem Inflammatory Syndrome in Children Associated With COVID-19. A Case Report - Ruiz-Rodríguez, Juan Carlos; Chiscano-Camón, Luis; Palmada, Clara; Ruiz-Sanmartin, Adolf; García-de-Acilu, Marina; Plata-Menchaca, Erika; Perurena-Prieto, Janire; Hernandez-Gonzalez, Manuel; Pérez-Carrasco, Marcos; Soler-Palacin, Pere; Ferrer, Ricard (Frontiers in Immunology, 2021)
Multisystem Inflammatory Syndrome in Children associated with COVID-19 (MIS-C) is characterized by hypercytokinemia leading to excess inflammation . We describe the use of an hemadsorption device in the supportive treatment of this cytokine storm.